Sentido De Experiencias Transformadoras De Mujeres Con Hijos En Condición De Discapacidad (2024)
The research presented sought to understand the meaning of the transformative experiences of women with children with disabilities, in the Municipality of Zarzal, Valle del Cauca; understanding that disability is a physical, mental, sensory, or intellectual limitation. According to information from the World Health Organization (WHO), around 15% of the population lives with some type of disability, with mothers and/or women being caregivers who assume this responsibility for care, with other roles in life being affected but Without a doubt they also transform the meaning, encompassing the totality in dedication, love and commitment. Therefore, the specific objectives were proposed to describe the characteristics of the couple's relationship, compared to the expectations of having a child; the identification of the development of the exercise of the parental role in the process of acceptance of a child with disabilities and the explanation of the process of personal transformation of mothers of children with disabilities. Theoretically, it is based on the theoretical perspectives of the meaning of life proposed by (Frankl V., 1991), who proposes that the human being's will for meaning is what can keep him afloat in the face of adversity. Likewise, it addresses the familiar theoretical perspectives of (Minuchin, 2004) and (Musitu, 2016), with the aim of interpreting how the participants have responded to adversities. Methodologically, it has a qualitative, descriptive approach that uses the semi-structured interview and life history technique to collect information; in order to specify those factors that influence the construction of meanings of life from adverse moments; The approach is phenomenological, focusing on the individual and subjective experiences of the participants. As a result, mothers who have lived this process with their children have applied meaning to life based on creative value, their experiences and attitudes under hope and resilience, where family support is imperative.